Case Report: A Rare Case of Acute Anterior Myocardial Infarction Simultaneously Associated With Aortic Mural Thrombosis Due to Essential Thrombocytosis - Ye, Sheng; Xia, Wu-jie; Chen, Peng (Frontiers in Cardiovascular Medicine, 2022)
Background: Essential thrombocytosis simultaneously complicated with acute myocardial infarction and aortic thrombosis is an extremely rare clinical occurrence with poor prognosis. Case: A 54 year-old female was admitted to our emergency department with abdominal pain for 3 hours. V1-V3 ST-segment elevation in ECG lead to the diagnosis of acute anterior myocardial infarction. Coronary angiography demonstrated total occlusion of the proximal LAD，and the patient was treated by angioplasty and placement of a drug-eluting stent. Then the computed tomography angiography(CTA) demonstrated massive mural thrombus located in the descending aorta. Bone marrow biopsy confirmed the diagnosis of essential thrombocytosis. The patients was successfully treated by anticoagulation therapy combinate with hydroxyurea. Conclusion: At present, the clinical diagnosis and treatment of essential thrombocytosis complicated with acute myocardial infarction and aortic thrombosis are mostly base on literatures. Early target vessel revascularization，antiplatelet and anticoagulant combinate with cytoreductive therapy may improve the prognosis. Clinicians should comprehensive considering the risk of bleeding and thrombosis, and make individualized treatment strategy for these patients.